Metachronous adenocarcinoma and large cell neuroendocrine carcinoma of the colon - Kung-Hung Lin; Nai-Jen Chang; Li-Ren Liou; Ming-Shan Su; Min-Jen Tsao; Meng-Lin Huang (Formosan Journal of Surgery, 2018)
Neuroendocrine tumors are a group of heterogeneous tumors originating from peptidergic neurons and neuroendocrine cells and can occur in many organs and tissues of the body. We reported a 77-year-old woman who had undergone a left hemicolectomy for descending colon adenocarcinoma 20 years previously, postoperatively; the final disease stage was T1N0M0 (Stage I). However, neuroendocrine carcinoma (NEC) at ascending colon with liver metastasis was found in a regular colonoscopy, accidentally. There are interesting with the findings in our case where the patient had an advanced stage of NEC in the ascending colon and an early-stage adenocarcinoma in the descending at the different time. She refused any palliative therapy even though she died 8 months postoperatively. To our best knowledge, this is the first case of metachronous adenocarcinoma and large-cell NEC at the different side of the colon. We believe surmise that previous adenocarcinoma of descending colon should be included in the risk factor even if the patient stood well after the operation in the follow-up.